The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1037/hea0000365
|View full text |Cite
|
Sign up to set email alerts
|

Targeting implicit approach reactions to snack food in children: Effects on intake.

Abstract: Targeting implicit reactions to high-energy snacks proved effective in decreasing intake of snacks in children. Furthermore, the previously reported stimulating effect of food promoting advergames on intake may disappear when a short cognitive task is presented directly after the game. Future work should evaluate the clinical implications of these findings. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 25 publications
2
63
0
Order By: Relevance
“…However, another study employed go/no-go training using jelly candy as no-go items and cute animals as go items. This study observed decreased intake of the trained food (jelly candy) and an untrained food (M&Ms) to the same degree [21]. Similarly, a recent study showed that food no-go (relative to go) training reduced intake of both trained and untrained unhealthy foods in a buffet taste test [22].…”
Section: Research Agendamentioning
confidence: 84%
See 3 more Smart Citations
“…However, another study employed go/no-go training using jelly candy as no-go items and cute animals as go items. This study observed decreased intake of the trained food (jelly candy) and an untrained food (M&Ms) to the same degree [21]. Similarly, a recent study showed that food no-go (relative to go) training reduced intake of both trained and untrained unhealthy foods in a buffet taste test [22].…”
Section: Research Agendamentioning
confidence: 84%
“…There are also stop-signal variants of this training procedure, but these variants are, as we will briefly discuss afterward, crucially different on a number of features (e.g., [18–20]). The control condition consists of a go/no-go training with non-food images (e.g., [21]) or a (go/no-go) task in which they respond to food images (e.g., [11]).…”
Section: What Is Food Go/no-go Training?mentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, warning children about the dire effects on their future health prospects of not eating healthy food, or just explaining them that a food is “healthy”, may well even reduce their acceptance of such food (Wardle et al, 2003). Novel methods to facilitate behavioral changes are needed, that do not relay on conscious intentions, but focus more on automatic processes (Papies, 2016, Folkvord et al, 2016c, Hollands et al, 2016). The memory-game that was used in this study can be seen as an example of such a novel method.…”
Section: Discussionmentioning
confidence: 99%